Eksplorasi Skill Kepemimpinan Kepala Sekolah sebagai Pemimpin di Satuan Pendidikan - Nasib Tua Lumban Gaol; Kevin Rade Siahaan (Manajemen Pendidikan, 2021)
School leadership is a crucial topic in the improvement of education quality through the role of educational leaders in leading and managing schools effectively and efficiently. Accordingly, the quality of the school leadership is urgent to discuss further. In particular, school leadership skill is an urgent component of which must be carried by the leader if the school will be successful. The main purpose of this study is to explore the school principal skills. A narrative literature review was used to conduct this study in order to investigate and describe the school leadership skills. Based on the result of the review, it was identified the five school leadership skills that can be implemented in the practice of the Indonesian school context. Those skills consist of time management, strategic management, cognitive, interpersonal, and decision-making. All skills are fundamental aspects to build for the betterment of educational management, particularly in managing the school. Theoretically and practically contributions of this study were discussed. Therefore, various research and literature reviews are recommended to conduct for the establishment of the school leadership unity for the Indonesian school context.